Study of the Effectiveness of Titanium Dioxide (TiO2) nanoparticle in Polyethersulfone (PES) Composite Membrane for Removal of Oil in Oily Wastewater - Shahruddin, Munawar Zaman; Zakaria, Nuratikah; Diana Junaidi, Nurul Fattin; Alias, Nur Hashimah; Othman, Nur Hidayati (Journal of Applied Membrane Science & Technology, 2017)
Polyethersulfone/Titanium oxide (PES/TiO2) composite membranes at various compositions of TiO2 nanoparticle (0, 0.1 and 0.5 wt. %) were prepared via phase inversion method. The prepared composite membranes were then tested for degradation process and separation process for oily wastewater. It was found that the addition of TiO2 that possess visible-light response activity led to an improvement of the membrane performances especially in photocatalytic activities. The membrane performances were also investigated by using liquid separation system in order to obtain the flux/permeation rate and also the percentage of oil removal by the membranes. The results indicate that the increment the amount of TiO2 nanoparticle in the composite membrane reduced the permeation flux. Further study has been made by characterizing the membranes in terms of contact angle, Field Emission Scanning Electron Microscope (FESEM), Fourier Transform Infrared Spectrometer (FTIR) and X-Ray Diffraction (XRD) analysis. The characterization results indicate that the TiO2 nanoparticles were uniformly mixed in the membrane. The increased of membrane hydrophilicity was demonstrated by the contact angle measurement. By adding TiO2, the membrane hydrophilicity was observed to be better than the neat PES composite membrane. Cross sectional images from FESEM also indicate that the addition of TiO2 nanoparticles help in increasing the macro-void of the membranes. Finally, a comparison between neat PES membrane and PES/TiO2 nanoparticle membrane proved that addition of TiO2 nanoparticle can be one of the ways to maximize the removal of oil.